And yet it moves - Erin Stalcup (Break away books, 2016)
"The stories in this volume are original in concept and execution, clearly informed but not constrained by contemporary trends in fiction. The narrative sensibility is intelligent and highly personal, attuned to all that is askew in contemporary culture but nonetheless especially interested in acts of generosity and kindness. Stalcup is a writer who manages to suggest the possibility of goodness without sacrificing a tough-minded insistence on reporting foibles and follies, often of the comic variety. Beyond its interest in narrative innovation, And Yet It Moves is an important collection because of its successful exploration of the territory that exists in the intersections between scientific, cultural, and spiritual theory and philosophy. And Yet It Moves has a well-defined target audience of readers interested in innovative fiction, and is a likely candidate for adoption in graduate fiction workshops and courses in innovative fiction" --